Structural and functional integrity of decontaminated N95 respirators: Experimental results. Issue 5 (June 2022) - Sharma, Sumit; Wang, Fang; Kumar, Shubham; Nawal, Ruchika R; Kumar, Priya; Yadav, Sudha; Szenti, Imre; Kukovecz, Akos; Schiller, Ulf D; Rawal, Amit
With the recent emergence of highly transmissible variants of the novel coronavirus SARS-CoV-2, the demand for N95 respirators is expected to remain high. The extensive use of N95 respirators by the public is susceptible to demand‐supply gaps and raises concern about their disposal, threatening the environment with a new kind of plastic pollution. Herein, we investigated the filtration performance of the N95 respirator by specifically analyzing the structure in the key filtration layers of meltblown nonwoven after decontamination with one and five cycles of liquid hydrogen peroxide, ultraviolet radiation, moist heat, and aqueous soap solution treatments. With the aid of X-ray microcomputed tomography (microCT) analysis, the local structural heterogeneity of the meltblown nonwoven has been unfolded and subsequently correlated with their filtration performance at a face velocity that matched with speaking conditions (∼3.89 m/s). The filtration efficiency results of the N95 respirator remain unaltered after performing one cycle of treatment modalities (except autoclave).